Usefulness of GeneXpert MTB/RIF in the diagnosis of extra-pulmonary tuberculosis (BIRDEM Medical Journal, 2021)
Background: Diagnosis of extra-pulmonary tuberculosis (TB) is often delayed because of diverse clinical presentations and difficulties in establishing the bacteriological diagnosis. This study aimed to evaluate usefulness of GeneXpert MTB/RIF in the diagnosis of extra-pulmonary TB in Bangladeshi patients.Methods: This cross-sectional study was done in BIRDEM General Hospital, Dhaka, Bangladesh from 2013 to 2016 as a part of Bangladesh Diabetic Somiti (BADAS)-USAID-TB Care-II project. Representative samples from 590 clinically suspected extra-pulmonary TB cases were tested for GeneXpert MTB/RIF along with conventional methods.Results: Total patients were 590 [mean age 43.9 (range 1-95) years] with male predominance (326, 55.3%). Most (513, 86.9%) patients were diabetic and new (574, 97.3%) TB suspects; while 16 (2.7%) patients had past history of TB. Common samples were pleural fluid (125, 21.2%), urine (110, 18.6%), cerebrospinal fluid (CSF) (91, 15.4%), pus (82, 13.9%), tracheal aspirates (57, 9.7%), ascitic fluid (45, 7.6%), gastric lavage (31, 5.3%), broncho-alveolar lavage (BAL) (18, 3.1%), lymph node aspirates (11, 1.9%) and synovial fluid (8, 1.4%). Among 590 samples, 68 (11.5%) were positive for Mycobacterium tuberculosis. Diagnostic yield was common for lymph nodes (4/7, 57.1%), pus (25/82, 30.5%), BAL (4/18, 22.2%), tracheal aspirates (8/57, 14.0%), urine (7/110, 6.4%), CSF (6/91, 6.6%) and pleural fluid (7/125, 5.6%). Of the 68 GeneXpert MTB/RIF positive samples, 52 (76.1%) were rifampicin sensitive, 16 (23.9%) showed intermediate sensitivity and none of the samples was resistant to rifampicin.Conclusions: GeneXpert MTB/RIF appeared as useful tool for diagnosing extra-pulmonary TB.Birdem Med J 2021; 11(2): 121-124